2014
DOI: 10.1063/1.4891238
|View full text |Cite
|
Sign up to set email alerts
|

Tunable electronic structures of p-type Mg doping in AlN nanosheet

Abstract: The p-type impurity properties are investigated in the Mg-doped AlN nanosheet by means of first-principles calculations. Numerical results show that the transition energy levels reduce monotonously with the increase in Mg doping concentration in the Mg-doped AlN nanosheet systems, and are lower than that of the Mg-doped bulk AlN case for the cases with larger doping concentration. Moreover, Mg substituting Al atom is energy favorably under N-rich growth experimental conditions. These results are new and intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 53 publications
5
18
0
Order By: Relevance
“…However, while in a 3D system the jellium is contained within bulk, in a 2D system it extends into vacuum and, as a consequence, the Coulomb energy of the system diverges as ∞. A number of studies for 2D charged defects have been based on such an approach, reporting widely-spread results with arbitrarily chosen [9,10,[13][14][15][16]. For almost two decades [20], this problem has remained unresolved, despite the importance of studying charged surface defects and catalysis involving charged species at surfaces.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, while in a 3D system the jellium is contained within bulk, in a 2D system it extends into vacuum and, as a consequence, the Coulomb energy of the system diverges as ∞. A number of studies for 2D charged defects have been based on such an approach, reporting widely-spread results with arbitrarily chosen [9,10,[13][14][15][16]. For almost two decades [20], this problem has remained unresolved, despite the importance of studying charged surface defects and catalysis involving charged species at surfaces.…”
mentioning
confidence: 99%
“…This has prompted an intense study of defect properties in 2D materials including a number of firstprinciples calculations, for example, for monolayer BN [9,10], MoS 2 [11,12], GaN [13], AlN [14], GaS/GaSe [15], and SnS 2 [16].…”
mentioning
confidence: 99%
“…Li et al [38] investigated the structural, electronic, and magnetic properties of AlN nanosheets by means of first-principles calculations. Peng et al [39] have theoretically pointed out that the transition energy levels reduce monotonously with the increase in Mg doping concentration in AlN nanosheets. Several theoretical works have related to the 1D AlN nanostructures by considering the geometry and electronic structures of AlN nanotubes or nanoribbons [38,[40][41][42], the piezoelectric properties [43] and the surface effects of AlNNWs [44,45], the electronic structures of the coaxial nanocables of Al-NNW core and carbon/BN nanotube shell [46], the hydrogen storage property of AlNNWs [47,48], and the structural and electronic properties of GaN-AlN nanotubes and nanowires [49,50].…”
Section: Introductionmentioning
confidence: 98%
“…Using first-principles calculations, Sandhya et al have found that both the polar and non-polar surfaces of Mg doped AlN are magnetic [37]. Some works have focused on two dimensional AlN [38,39]. Li et al [38] investigated the structural, electronic, and magnetic properties of AlN nanosheets by means of first-principles calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Their work showed that a perfect h‐AlN sheet was only 6% less stable than bulk wurtzite AlN from the perspective of cohesive energy. As we well known, the properties of these nanosystems can sometimes be precisely regulated or even tailored by modifying the structures or chemical compositions, transition metal‐ (TM) doped and p‐type magnesium‐doped AlN nanosheets are investigated by means of first‐principle calculations . The calculations indicate that some TM atoms doped AlN nanosheets with half‐metal characters seem to be nice candidates for spintronic devices, while the stoichiometric AlN nanosheet is nonmagnetic.…”
Section: Introductionmentioning
confidence: 99%